The accountant's role in the IT environment: A Malaysian perspective - Zainal, Aniza; Abdullah, Akilah; Ismail, Nor Azizi (2000)
This paper is specially designed to look into the contemporary role of accountant in the IT environment particularly in Malaysian perspective. Most of the literature suggests that the accountants' response to the computer technology will anticipate changes in their existing roles. The objectives of this study are (1) to indicate the contemporary view of accountant's role in the IT environment, and (2) to what extend does IT influences the existing accountants roles. During this few years, there were a lot of discussions about the role of accountants. Like many other professions, accounting has been greatly affected by changes in a dynamic environment. Hence, society expects accountants to keep abreast of relevant developments and ensure that professional accountants continue to deal effectively with challenges faced in the profession. The method used in this research is based on an opinion survey of practicing accountants by mailing questionnaires. The results indicates that the accountant's role, particularly in the organization is confronted with a new demand. As most of the accounting process had been computerized, accountants are insisting on becoming involved with business activities. After all, accountants nowadays have to grasp new skills and knowledge to accommodate their roles within organizations.